The Remedy - Young, Suzanne (New York : Simon Pulse, 2015)
Seventeen-year-old Quinn provides closure to grieving families by taking on the short-term role of a deceased loved one, until huge secrets come to the surface about Quinn's own past.
Companion book to: The Program and The Treatment.
Keywords: Death -- Fiction; Grief -- Fiction; Identity -- Fiction; Memory -- Fiction; Science fiction; Young adult fiction